An Empirical Study on the Determinants of Corporate Dividend Policy in the UK - Wang, Peng (2013)
This study examines the determinants of corporate dividend policy in the UK. The analysis is based on 1430 firm-year observations of 130 non-financial companies which paid dividends annually from 2002 to 2012. The present study re-examines the most relevant theories of dividend policy and identifies fourteen potential driving factors of dividend policy. Both firm characteristic factors and corporate governance factors have been included. A comparative research is then presented using the Generalised Method of Moments (GMM) and the two-step multivariate procedure (factor analysis and multiple regression). The results of the GMM estimation indicate that firm size, profitability, growth, free cash flows, board size and lagged dividends have positive impacts on dividend policy while firm’s risk, leverage,liquidity, tangibility and board independence have negative effects. Furthermore, retained earnings to equity ratio as a proxy to firm’s life-cycle stage affects dividend decisions positively. The results of the factor analysis clarify that there is no significant misspecification in variable selection. The findings of the multiple regression confirm the consistency of the GMM estimation. Using the two approaches not only provides more reliable regression results but also clarifies the rationality of this study. The two regression approaches jointly demonstrate that ten of the pre-identified factors have significant impacts on the dividend policy in the UK, which could be summarised as follows. First, large and profitable companies pay more dividends. Second, risky and highly levered companies pay fewer dividends. Third, firms with sufficient funds (free cash flows and retained earnings) pay more dividends. Fourth, board independence (board size) is negative (positive) related to dividend policy. Finally, there are strong significant evidences on the positive effects of lagged dividends.